The Us Federal Debt Outlook : Reading the Tea Leaves - Celasun, Oya (IMF Working Papers; Working Paper, 2010)
We show that fiscal policies reflecting a primary balance response to higher debt in line with historic experience would significantly increase the likelihood of reaching the debt targets of the U.S. administration in the medium term. Deficits and debt are higher under current budgetary proposals and IMF projections for real activity and interest rates, which do not include a reaction of policies to rising primary deficits. Under the IMF staff's current economic projections, a primary fiscal adjustment of about 3.5 percent of GDP would be needed to achieve a debt level of about 70 percent of GDP in 2020.